Disparities in adult women's access to contraception during COVID-19: a multi-country cross-sectional survey - Cavagnis, Sara; Ryan, Rebecca; Mussa, Aamirah; Hargreaves, James R.; Tucker, Joseph D.; Morroni, Chelsea (Frontiers in Global Women's Health, 2024)
During the COVID-19 pandemic, family planning services over the world have been disrupted. There are still uncertainties about the impact on access to contraception, particularly among marginalised populations. This study aimed to assess the effect of COVID-19 on women's access to contraception, focusing on those experiencing loss of income and self-isolation. The International Sexual Health and Reproductive Health (I-SHARE) survey collected data from 5,216 women in 30 countries. Multivariable logistic regression was conducted to assess the association between loss of income during the pandemic, self-isolation and reduced access to contraception. Women experiencing loss of income and those who had self-isolated had reduced access to contraception (respectively aOR 2.3 and 1.7, for both p < 0.001). Most women reported inaccessibility of health centres, fear of COVID-19, and stockouts as reasons for reduced access. This study highlights how socio-demographic differences may have impacted access to contraception during the pandemic. People experiencing income loss and self-isolation might have faced increased barriers to family planning during the pandemic. Contraception should be prioritised in times of crisis: when planning services, financial support, telehealth and other measures should be implemented in order to increase access and reduce inequalities.